Factors influencing the health-related quality of life of postmenopausal women with diabetes and osteoporosis: a secondary analysis of the Seventh Korea National Health and Nutrition Examination Survey (2016-2018) - Hyuk Joon Kim; Hye Young Kim (Korean Society of Women Health Nursing, 2022)
Purpose The prevalence of osteoporosis in postmenopausal women is increasing, and diabetes patients have decreased bone density. Their health-related quality of life (HRQoL) is diminished by the resultant physical dysfunction and depression. The purpose of this study was to identify factors influencing HRQoL in postmenopausal women with diabetes and osteoporosis. Methods This was a secondary data analysis of the Seventh Korea Health and Nutrition Examination Survey (2016-2018), which utilized a complex, multistage probability sample design. The participants in the study were 237 women with diabetes and osteoporosis. To evaluate the factors that influenced HRQoL, a complex-samples general linear model was constructed, and the Bonferroni correction was performed. Results In this sample of women aged 45 to 80 years (mean±standard deviation, 71.12±7.21 years), the average HRQoL score was 0.83±0.18 out of 1.0. Factors influencing HRQoL were age (70s: t=-3.74, p<.001; 80s: t=-3.42, p=.001), walking for exercise more than 5 days a week (t=-2.83, p=.005), cerebrovascular disease (t=-8.33, p<.001), osteoarthritis (t=-2.04, p=.014), hypertension (t=2.03, p=.044), higher perceived stress (t=-2.17, p=.032), poor glycemic control (t=3.40, p=.001), waist circumference (t=-2.76, p=.007), sitting time per day (t=-2.10, p=.038), and a longer postmenopausal period (t=3.09, p=.002). Conclusion In order to improve the HRQoL of postmenopausal women with osteoporosis and diabetes, it is necessary to implement intervention strategies that enable the effective management of chronic diseases, while preventing the complications of diabetes and minimizing stress through physical activity.